2021
DOI: 10.1029/2020sw002531
|View full text |Cite
|
Sign up to set email alerts
|

A Peculiar ICME Event in August 2018 Observed With the Global Muon Detector Network

Abstract: Solar eruptions such as coronal mass ejections (CMEs) cause environmental changes in various ways in near Earth space. It is known that major geomagnetic storms can be triggered by the arrival of an interplanetary counterpart of a CME (ICME) at Earth along with a strong southward interplanetary magnetic field (IMF), which allows solar wind energy and plasma to enter the magnetosphere. A magnetic flux rope (MFR), which is often observed in an ICME with magnetic field lines winding about the central axis, is rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…By analyzing the GMDN data recorded during this event, we found that a significant increase of the GCR density (omnidiectional intensity) exceeding the unmodulated level before the shock was observed for 6 h between 04:00 and 09:00 on 26 August, near the trailing edge of the MFR. Significant north directed anisotropy was also found during the same 6 h (Kihara et al, 2021). Although it is out of scope of this paper to describe our analysis of this event, observed by the GMDN in detail, we show how the data recorded by Syowa NM and MD are consistent with the observation by the GMDN.…”
Section: Preliminary Observations and Data Analysissupporting
confidence: 67%
“…By analyzing the GMDN data recorded during this event, we found that a significant increase of the GCR density (omnidiectional intensity) exceeding the unmodulated level before the shock was observed for 6 h between 04:00 and 09:00 on 26 August, near the trailing edge of the MFR. Significant north directed anisotropy was also found during the same 6 h (Kihara et al, 2021). Although it is out of scope of this paper to describe our analysis of this event, observed by the GMDN in detail, we show how the data recorded by Syowa NM and MD are consistent with the observation by the GMDN.…”
Section: Preliminary Observations and Data Analysissupporting
confidence: 67%
“…We finally note a significant softening of the first-order anisotropy in the MFR period as indicated by γ 1 (blue curve in Figure 3(d)). So far γ 1 ∼ 0 has been assumed in analyses of the anisotropy observed by GMDN (e.g., Kihara et al 2020) based on the diffusive GCR transport picture in which the first-order anisotropy is expressed in terms of the diffusion balancing with the rigidity independent solar wind convection. However, γ 1 in Figure 3(d) might be indicating that the diffusive transport picture is not appropriate in the MFR period of this event.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…While most of the preceding studies using the NM network and GMDN separately have been limited to analyze the variations of the GCR density and the first-order anisotropy (Belov et al 2018;Tortermpun et al 2018;Kihara et al 2020), the second-order anisotropy also has a significant contribution to the GCR variation in some events. Bidirectional streaming (BDS) is often observed in satellite measurements of lowenergy electrons and ions indicating particles trapped in the MFR in which the field line is anchored on Sun at both ends.…”
Section: Introductionmentioning
confidence: 99%
“…for the whole solar magnetic cycle, also considering high energy GCRs, especially the from Princess Sirindhorn Neutron Monitor, with vertical cut-off rigidity 16.8 GV (e.g. Deeprom and Nutaro, 2017) and muon telescopes from the Global Muon Detector Network (Kihara et al, 2021). We will continue to test the structure-function and detrended-fluctuationanalysis methods, focusing on the influence of different trend-removal techniques (Kantelhardt et al, 2001).…”
Section: Discussionmentioning
confidence: 99%